Penggunaan pujian dalam bahasa cina oleh guru wanita dan lelaki / Teoh Huoi She - Teoh, Huoi She (2012)
This purpose of this study is to examine compliment among secondary school teachers in Chinese language. Therefore, this study tends to explore the common realizations of compliments in Chinese language which used by female and male teachers in the classroom. In addition, this study also to explore lexical and syntactic patterns of Chinese compliments. The data of the present study are based on the conversation in the classroom which has been recorded and transcribed. Jefferson Transcription System (1978) adapted and modified to analyze the conversation in Chinese language. The study was obtained on the analytical framework established by Ye (1995) and Wang (2003). Qualitative method is used to illustrate the realization compliment of gender, while the frequency is shown as percentage by analyzing the data. The results show that female and male teachers were found realize explicit compliment, compliment implicit and no compliment, but they didnt not use strategie no response while teaching in class. This finding is consistent with results reported by Ye (1995), but it is slightly different. However, the compliment given to the students is different between men and women teachers, where female teachers are more likely to use compliment, especially explicit compliment. The results shows that the overwhelming majority of Chinese compliments contain a high restricted set of adjectives, where it is consistent with the findings of Wolfson (1983). The most commonly used adjectives by female and male teachers are those with positive semantic meaning 好 (hǎo / good), 对 (duì / right) and 准确 (zhǔnquè / accurate / correct). However, they differ in the use of adverbs and verbs when complimenting. The most often syntactic patterns used by female and male teachers are adjective (ADJ) + [particle (PART)] and combination of adverbs (ADV) + adjective (ADJ). Instead, they also show differences in the selection of syntactic patterns when complimenting the students. Female teachers are more likely to choose a combination of a noun or noun phrase [(KN / FN)] + verb (KK) + adverbs (ADV) + adjective (ADJ), while the male teachers prefer to use syntactic pattern comparison (比 bǐ). In addition, female teachers prefer to use proper names, especially names of students, while male teachers are more often to use pronouns 这 (zhè / this) to compliment. Finally, this study hopes to contribute to linguistics and encourage other researchers to explore the field of language and gender.